Methionine Hydroxy Analog Supplementation to Increase Feed Utilization for Indigenous Sheep - Bambang Waluyo Hadi Eko Prasetiyono; Mulyono Mulyono; Widiyanto Widiyanto (Jurnal Sain Veteriner, 2020)
In the tropical area, productivity of ruminant has not optimized caused by the low quality of nutrition that leads to low-efficiency metabolism at the level of ruminal fermentation, post rumen digestibility, and intermediary metabolism. The study aimed to analyze effect of methionine hydroxy analog (MHA) on ruminal fermentation profiles of indigenous sheep specifically in the increase of ruminant productivity. In vitro utility test was conducted using rumen fluid of the indigenous sheep and sample of rational ration having a proportion of grass and concentrate 30%:70%, dry matter basis. The treatments implemented were three levels of MHA supplementation; T0: 0 g/day, T1: 3 g/day, and T2: 6 g/day. Variables measured were dry matter digestibility (DMD), organic matter digestibility (OMD), production of VFA, NH3, as well as total protein, and molar proportion of partial VFA of rumen fluid. Data were analyzed using analysis of variance (ANOVA) in a completely randomized design (CRD). The 0.2% MHA supplementation increased OMD with the highest production of total protein was from 28.57 mg/g (T0) to 40.49 mg/g (T2) (P<0.05). Meanwhile, the lowest ratio of acetate : propionate was from 2.74 (T0) to 2.33 (T2) (P<0.05). Supplementation of MHA up to 6 g/day concentrate increased the performance of fermentation and/or feed utility.